Protecting the Airway and the Physician: Lessons from 214 Cases of Endotracheal Intubation Litigation. (18th October 2022) - Eloy, Jean Daniel; Pashkova, Anna A.; Amin, Molly; Anthony, Christy; Munoz, Daisy; Gubenko, Yuriy; Patel, Shivani; Korban, Anna; Perales, Andrea; Svider, Peter F.; Eloy, Jean Anderson
Abstract : Objective . Medicolegal examination of an intervention as common as endotracheal intubation may be valuable to physicians in many specialties. Our objectives were to comprehensively detail the factors raised in litigation to better educate physicians on strategies for minimizing liability and augmenting patient safety. Methods . Publicly available court records were searched for pertinent litigation. Ultimately, 214 jury verdict and settlement reports were examined for various factors, including outcome, award, geographic location, defendant specialty, setting in which an injury occurred, patient demographics, and other causes of malpractice. Results . Ninety-two cases (43.0%) were resolved in the defendant's favor, with the remaining cases resulting in out-of-court settlement or a plaintiff's verdict. Payments from these cases were considerable, averaging $2.5 M. The most frequent physician defendants were anesthesiologists (59.8%) and emergency-physicians (19.2%), although other specialties were well represented. The most common setting of injury was the operating room (45.3%). Common factors included sustaining permanent deficits (89.2%), death (50.5%), and anoxic brain injury (37.4%). Injuries occurring in labor and delivery mostly involved newborns and had among the highest awards. Conclusions . Litigation involves injuries sustained in numerous settings. The most common factors present included sustaining permanent deficits, including anoxic brain injury. The presence of this latter injury increased the likelihood of a case being resolved with payment. Finally, deficits in informed consent were noted in numerous cases, stressing the importance of a clear process in which the physician explains specific risks (such as those detailed in this analysis), benefits, and alternatives.